2016
DOI: 10.1002/mus.25120
|View full text |Cite
|
Sign up to set email alerts
|

Six-minute walk test is reliable and valid in spinal muscular atrophy

Abstract: This study documents measurement properties of reproducibility, positive criterion validity, and convergent validity with established clinical assessments and reaffirms the value of the 6MWT as a pivotal outcome measure in SMA clinical trials. Muscle Nerve 54: 836-842, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 54 publications
2
79
1
2
Order By: Relevance
“…Ambulatory children and adolescents treated with nusinersen in the CS2 multiple‐dose and CS12 extension studies demonstrated improvements in ambulatory function (6MWT), with clinically meaningful increases in walking distance and modest decreases or stabilization in fatigue. Although there is no precedent for improvements like these in individuals with SMA, changes of ≥30 meters in 6MWT distance are considered clinically meaningful and to impact everyday activities in other pediatric neuromuscular disorders …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambulatory children and adolescents treated with nusinersen in the CS2 multiple‐dose and CS12 extension studies demonstrated improvements in ambulatory function (6MWT), with clinically meaningful increases in walking distance and modest decreases or stabilization in fatigue. Although there is no precedent for improvements like these in individuals with SMA, changes of ≥30 meters in 6MWT distance are considered clinically meaningful and to impact everyday activities in other pediatric neuromuscular disorders …”
Section: Discussionmentioning
confidence: 99%
“…Tools assessing walking ability and fatigue are clinically relevant in individuals with milder forms of SMA . The 6‐minute walk test (6MWT) is a valid and clinically meaningful measure of ambulatory function and has demonstrated sensitivity to fatigue‐related changes in individuals with SMA . Fatigue measured during the 6MWT may represent underlying disease‐specific mechanisms, and improvements may represent treatment benefit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6‐minute walk test (6MWT) measures the maximum distance a person can walk in 6 minutes over a 25‐meter linear course. It has been shown to be a valid and reliable assessment of exercise capacity and functional walking ability, and it can capture physiological fatigue in patients with SMA . Distance walked over the entire 6‐minute time period, distance covered each minute, and the time to complete each 25‐meter interval were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The 6‐Minute Walk Test (6MWT) is a self‐paced walking test that measures the distance an individual is able to walk on a hard, flat surface for 6 min . Originally developed for assessment of aerobic activity in patients with respiratory disease, the 6MWT is now validated in numerous other patient populations, including those with musculoskeletal diseases (eg, Duchenne/Becker muscular dystrophy, facioscapulohumeral muscular dystrophy, spinal muscle atrophy), and has been used as an efficacy measure in clinical studies of patients with muscular and metabolic disorders. The 6MWT has also been used as an outcome measure in clinical studies of patients with other rare diseases, such as Pompe disease, Hunter syndrome, and Morquio A syndrome .…”
Section: Introductionmentioning
confidence: 99%